2007
DOI: 10.1093/ajcn/86.3.714
|View full text |Cite
|
Sign up to set email alerts
|

An association of serum vitamin D concentrations < 40 nmol/L with acute respiratory tract infection in young Finnish men

Abstract: Clinical trials of vitamin D supplementation are needed to investigate whether it enhances immunity to microbial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
264
3
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(282 citation statements)
references
References 17 publications
11
264
3
4
Order By: Relevance
“…14 Cathelicidin transcription is particularly dependent on sufficient circulating levels of 25(OH)D. 14,33 The findings of the present study are consistent with these biologic principles and other epidemiologic reports linking low serum 25(OH)D levels to increased risks of infection in the nondialysis population. 34,35 The present study makes an important contribution to the literature by demonstrating this association in the chronic dialysis population and provides another plausible mechanism for the well known impaired immunity in these patients. The exact mechanisms by which 25(OH)D may protect against CVD have not been fully delineated.…”
Section: Discussionsupporting
confidence: 62%
“…14 Cathelicidin transcription is particularly dependent on sufficient circulating levels of 25(OH)D. 14,33 The findings of the present study are consistent with these biologic principles and other epidemiologic reports linking low serum 25(OH)D levels to increased risks of infection in the nondialysis population. 34,35 The present study makes an important contribution to the literature by demonstrating this association in the chronic dialysis population and provides another plausible mechanism for the well known impaired immunity in these patients. The exact mechanisms by which 25(OH)D may protect against CVD have not been fully delineated.…”
Section: Discussionsupporting
confidence: 62%
“…The principal physiological function of 1,25(OH) 2 D 3 is enhancing the absorption of calcium and phosphate from the intestinal tract, therefore positively regulating bone formation [9][10][11] . To date, several lines of epidemiological and experimental findings have supported the links of vitamin D with various conditions or diseases beyond bone health [3] , including muscle function [12,13] , autoimmune diseases [14] , cancer [15,16] , cardiovascular diseases (CVD) [17][18][19] , hypertension [20,21] , diabetes [22] , inflammatory diseases [23] , and all-cause mortality [24] , etc.…”
Section: General Roles Of Vitamin D In Physiological Conditions and Dmentioning
confidence: 99%
“…Previous studies have reported associations between low serum 25(OH)D concentration and increased occurrence of RTI (2,18,19) . However, other studies performed in selected populations have not found a significant association (20,21) .…”
mentioning
confidence: 95%